ANTIOXIDANT MEDIATED DEFENSE ROLE OF ECLIPTAALBA HERBAL EXTRACT AGAINST CCL4 INDUCEDTOXIC HEPATITIS - Priya, G. (International Journal of Current Pharmaceutical Research, 2018)
Objective: The present study focuses on the antioxidant mediated protective effect of a popular medicinal herbEcliptaalba against CCl4induced oxidative stress in the liver of rats. Methods: Rats divided into four groups were administered with CCl4 andCCl4 along with methanol extract of leaves of Eclipta herb (200 and 400 mg/kg b. wt) for three weeks. At the end of treatment, rats were anaesthetized and blood samples were collected for serum separation. Biochemical analysis such as alanineaminotransferase (ALT), aspartateaminotransferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and total bilirubin (TB) were done in serum. Liver tissue was used for glutathione (GSH), lipid peroxidation (LPO), gluatathione peroxidase (GPx), glutathione Stransferase (GST), superoxide dismutase (SOD)and catalase (CAT) analysis. CCl4 administration caused significant elevation of the serum enzymes and total bilirubin content. Results: Antioxidant enzymes were drastically inhibited with significant reduction of glutathione and increased lipid peroxidation in CCl4 treated rats. Ecliptaalbaextracts administrated rats, however did not show much changes in marker enzyme level. Antioxidant enzyme status was also not affected and found nearer to the control levels. Increased gluatathione level and reduced lipid peroxidation was also evident in Eclipta alba treated rats. Conclusion: The findings show that Eclipta alba extract offers better protection against the free radical toxicity of CCl4.